Clinical Practice Guideline (Update): Earwax (Cerumen Impaction) Executive Summary. (January 2017) - Schwartz, Seth R.; Magit, Anthony E.; Rosenfeld, Richard M.; Ballachanda, Bopanna B.; Hackell, Jesse M.; Krouse, Helene J.; Lawlor, Claire M.; Lin, Kenneth; Parham, Kourosh; Stutz, David R.; Walsh, Sandy; Woodson, Erika A.; et al.
The American Academy of Otolaryngology—Head and Neck Surgery Foundation (AAO-HNSF) has published a supplement to this issue of Otolaryngology–Head and Neck Surgery featuring the updated Clinical Practice Guideline: Earwax (Cerumen Impaction). To assist in implementing the guideline recommendations, this article summarizes the rationale, purpose, and key action statements. The 11 recommendations emphasize proper ear hygiene, diagnosis of cerumen impaction, factors that modify management, evaluating the need for intervention, and proper treatment. An updated guideline is needed due to new evidence (3 guidelines, 5 systematic reviews, and 6 randomized controlled trials) and the need to add statements on managing cerumen impaction that focus on primary prevention, contraindicated intervention, and referral and coordination of care.